Wettability, interfacial tension (IFT) and viscosity alteration of nanofluids under electromagnetic (EM) waves for enhanced oil recovery (IFT) applications - Lee, K. (2019)
Zinc oxide (ZnO) nanoparticles (NPs) were prepared and synthesized via sol-gel method, by using citric acid as a precursor. The annealing temperatures were 500 and 800 Â°C which yielded average particle sizes of 56 and 117 nm, respectively. ZnO nanofluids of two different particle sizes (56 and 117 nm) were prepared using 0.1 wt nanoparticles that were dispersed into brine (3 wt NaCl) along with SDBS as dispersant. The impact of EM waves on wettability, viscosity and IFT of nanofluid was investigated. Results showed further reduction in wettability under EM influence with increased viscosity and reduced IFT. These results reveal a potential way to employ water-based ZnO nanofluids for enhanced oil recovery purposes at a relatively high reservoir temperature. Â© 2019, Springer International Publishing AG, part of Springer Nature.